Parenting, Social Norms and Adolescent Risky Behaviors - Donatella Lanari; Lucia Mangiavacchi; Luca Piccoli; Luca Pieroni (Institute of Labor Economics (IZA), 2025)
This study investigates the association between childhood parenting styles and the emergence of risk-taking behaviors in young adulthood, a critical life course transition. Utilizing data on risk-taking behaviors among college students, alongside variables reflecting parent-child relationships in the family of origin, we derive classifications of parenting styles. The empirical findings reveal that individuals exposed to authoritarian parenting, and to a lesser extent, permissive parenting, demonstrate an increased propensity for engaging in diverse risk-taking behaviors, both in frequency and intensity. Conversely, authoritative parenting appears to exert a partial mitigating influence on these behaviors. Furthermore, by analyzing a sub-sample of students who migrated to a different province to enroll in a University degree, we explore the impact of parental social norms prevalent in their provinces of origin on these behaviors, observing a limited effect. These findings contribute to the understanding of how family and environmental influences during critical life stages shape health-related behaviors and potentially impact life-course and human capital trajectories.
Keywords: D13; I3; J13; 330; parenting styles; risky behaviors; adolescence; social norms; culture